Perceptions of school counselors, teachers and principals of the necessity of teaching experience for school counselors - Dayya, Maya Imad (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2014)
This case study aimed at investigating and better understanding the perceptions of Lebanese school counselors, teachers and principals on whether teaching experience is necessary for school counselors to be competent in delivering the school counseling program (referring to guidance curriculum, responsive services, individual student planning and system support components). The sample for this study represented three private schools in Lebanon; a total of 27 participants including respectively three teachers, counselors and principals from each school across elementary, middle and high school levels. All participants took part in a semi-structured interview and filled in a survey to determine to what extent previous teaching experience can affect various counseling activities and hence allow school counselors to be successful at their jobs. Grounded theory was used in order to make meaning of the data collected from the interviews. Descriptive statistics were computed and presented in tables reflecting the data collected from the survey. There was a general agreement among participants that teaching experience was helpful but not necessary for school counselors. Participants believed that prior teaching for school counselors could help them with their jobs in several domains. Research findings from this current study will be presented to the universities in Lebanon that offer masters in school guidance and counseling as a baseline for feedback, reflections and modification if necessary within their programs.
: Mémoire
Keywords: Orientation et Conseil; School guidance and counseling